ЭКОЛОГИЯЛЫҚ ТƏЛІМ ТƏРБИЕ ТУРАЛЫ А. ҚҰНАНБАЙ ҰЛЫНЫҢ ДАНАЛЫҚ ОЙЛАРЫ (Experimental biology, 2015)
In the article the role of the promivent Kazakh author Abai Kunanbayev for ecological education of yong people in the ХХ cautry feginning is discussed.
Keywords: ecological education